2022
DOI: 10.15835/nbha50112615
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with different agents mitigate alkalinity induced oxidative damage and improves maize growth

Abstract: Soil alkalinity is a severe threat to crop production globally as it markedly retards plant growth. Different techniques are used to mitigate alkaline stress, but priming techniques are considered the most appropriate. The current study was carried out in complete randomized design (CRD) to evaluate the effect of different priming techniques on maize crop grown under different levels of alkalinity stress. The experiment was comprised of different treatments of alkalinity stress (AS) including, control, 6 dS m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…6). The above results are as per the findings of (33), who reported that the maximum stability in the membrane and the synthesis of the least amount of MDA along with the accumulation of osmolytes (proline content) and catalase activity in priming treatments reform the damage of morphological as well as biochemical to overcome from drought conditions (34,35). Furthermore, analysis of the correlation coefficient of studied parameters also provides a glimpse of the positive and negative relationships with priming treatments for drought tolerance (Table 2).…”
Section: Resultssupporting
confidence: 87%
“…6). The above results are as per the findings of (33), who reported that the maximum stability in the membrane and the synthesis of the least amount of MDA along with the accumulation of osmolytes (proline content) and catalase activity in priming treatments reform the damage of morphological as well as biochemical to overcome from drought conditions (34,35). Furthermore, analysis of the correlation coefficient of studied parameters also provides a glimpse of the positive and negative relationships with priming treatments for drought tolerance (Table 2).…”
Section: Resultssupporting
confidence: 87%
“…Drought stress also disturbs electron transport and decreases the pool size of electron acceptors ( Feng and Cao, 2005 ; Azzeme et al, 2016 ), also leading to marked reduction in photosynthesis. Drought-induced ROS also damage membrane integrity and cause oxidation of proteins, DNA, nucleic acid, lipids, and carbohydrates ( Sabra et al, 2012 ; Dossa et al, 2017 ; Hassan et al, 2019 , 2021 ; Bao et al, 2020 ; Jinhu et al, 2022 ; Khan et al, 2022a , b ). However, plants accumulate different osmolytes to counter the effects of DS.…”
Section: Plant Responses To Drought Stressmentioning
confidence: 99%
“…Salt stress is global issue which affects about 20% of agricultural area and reduce crop yield [ 10 ]. Among the many salts found in the soil, NaCl is the most common [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%